2008
DOI: 10.1111/j.1365-2354.2007.00865.x
|View full text |Cite
|
Sign up to set email alerts
|

The determinants of traditional Chinese medicine and acupuncture utilization for cancer patients with simultaneous conventional treatment

Abstract: This paper investigates the determinants of traditional Chinese medicine (TCM) and acupuncture utilization for cancer patients who are simultaneously having conventional Western medical treatments. This study used five leading cancers in Taiwan, namely cervical, breast, lung, liver and colorectal cancers. A total of 2499 cancer patients were interviewed, of which 2034 had full information and were analysed. Logistic regressions were used for both TCM and acupuncture. The results showed that type of cancer and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 17 publications
(52 reference statements)
0
33
0
2
Order By: Relevance
“…We screened 2879 abstracts from electronic search, and 39 full texts were retrieved for further assessment. With the application of exclusion criteria, 14 papers were considered ineligible . Finally, 25 studies from electronic searches were included.…”
Section: Resultsmentioning
confidence: 99%
“…We screened 2879 abstracts from electronic search, and 39 full texts were retrieved for further assessment. With the application of exclusion criteria, 14 papers were considered ineligible . Finally, 25 studies from electronic searches were included.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, TCM has a higher level of accessibility because of less financial barrier. A study on the determinants of TCM and acupuncture utilization of patients with cervical, breast, lung, liver, or colorectal cancers in Taiwan has shown that the prevalence of TCM and acupuncture use for lung cancer patients is 16.03% and 2.53%, respectively [11]. …”
Section: Introductionmentioning
confidence: 99%
“…Compared with CAM use by Western populations, TCM has a higher level of accessibility due to lesser financial barrier. A study on the determinants of TCM and acupuncture utilization of cancer patients in Taiwan has shown that the prevalence of TCM ranges from 14.81% for cervical cancer to 30.13% for breast cancer [8]. …”
Section: Introductionmentioning
confidence: 99%